1995
DOI: 10.1103/physrevlett.75.2602
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Multibubble and Single-Bubble Sonoluminescence Spectra

Abstract: Comparisons of the spectral characteristics of sonoluminescence from cavitation in bubble fields (MBSL) versus cavitation of single bubbles (SBSL) have been made for aqueous solutions under similar experimental conditions. In particular, alkali metal chloride solutions exhibit sonoluminescence emission from excited state Na or K atoms in MBSL, while SBSL exhibits no such emission. Since the metal ions are not volatile, participation of the initially liquid phase must occur in MBSL. Surface wave and microjet fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
126
0
8

Year Published

1998
1998
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(138 citation statements)
references
References 16 publications
2
126
0
8
Order By: Relevance
“…The standing ultrasound wave of the driving keeps the bubble in position at a pressure antinode and, at the same time, drives its oscillations. The experiments of Putterman's group (Barber & Putterman 1991;Barber et al (1994Barber et al ( , 1995; Hiller et al 1994;Löfstedt, Barber & Putterman 1993;Weninger, Putterman & Barber 1996) and others have revealed a multitude of interesting facts about SBSL: the width of the light pulse is small (Barber & Putterman 1991 give 50 ps as upper threshold, Moran et al 1995 10 ps -recent measurements by Gompf et al 1997 report 100-300 ps, depending on the forcing pressure and gas concentration in the liquid), the spectrum shows no features such as lines (Hiller, Putterman & Barber 1992;Matula et al 1995). While the exact mechanism of light emission is still an open issue, almost all suggested theories -see e.g.…”
Section: Sonoluminescencementioning
confidence: 99%
“…The standing ultrasound wave of the driving keeps the bubble in position at a pressure antinode and, at the same time, drives its oscillations. The experiments of Putterman's group (Barber & Putterman 1991;Barber et al (1994Barber et al ( , 1995; Hiller et al 1994;Löfstedt, Barber & Putterman 1993;Weninger, Putterman & Barber 1996) and others have revealed a multitude of interesting facts about SBSL: the width of the light pulse is small (Barber & Putterman 1991 give 50 ps as upper threshold, Moran et al 1995 10 ps -recent measurements by Gompf et al 1997 report 100-300 ps, depending on the forcing pressure and gas concentration in the liquid), the spectrum shows no features such as lines (Hiller, Putterman & Barber 1992;Matula et al 1995). While the exact mechanism of light emission is still an open issue, almost all suggested theories -see e.g.…”
Section: Sonoluminescencementioning
confidence: 99%
“…The complete photoemission spectrum associated with cavitation bubble collapse in water has yet to be determined. Previous studies showed only broad emission bands in the visible region of the electromagnetic wave spectrum characterized by the absence of any spectral peaks (17)(18)(19)(20)(21). The intensity of these spectra appears to increase continuously with frequency until the UV cutoff of water at 200 nm (18,21).…”
Section: Inverse Analysis Of Cavitation Impact Phenomena On Structuresmentioning
confidence: 99%
“…The intensity of these spectra appears to increase continuously with frequency until the UV cutoff of water at 200 nm (18,21). It is significant to note that there has been no previous evidence of UV emission from the bubble cavitational collapse due to the fact that photons of energies greater than 6 eV tend to be absorbed by water molecules (11,19). Next, when bubbles sustaining cyclic cavitation collapse due to an ultrasonic field are placed within the near neighborhood of a solid surface, symmetry conditions are disrupted such that the general morphology of cavitation bubble collapse transitions from that of spherically symmetric collapse (Fig.…”
Section: Inverse Analysis Of Cavitation Impact Phenomena On Structuresmentioning
confidence: 99%
“…A better knowledge of bubble-bubble interactions will be the first step towards understanding multi-bubble sonoluminescence (MBSL), the light emission by thousands of bubbles in a bubble cloud under oscillating high pressure. Here, the bubbles disturb one another, so the collapses are much weaker on average, and the spectra of the emitted light have distinct lines 7 , in contrast 6 to those of SBSL -implying that the gas in SBSL is so hot that emission lines are thermally smeared out. Ohl et al 3 have already taken a step towards studying bubble interactions by generating a bubble near a wall.…”
mentioning
confidence: 99%